An unusual presentation of ocular rosacea - Celiker,Hande (2017)
ABSTRACT Rosacea is a chronic, progressive disease of unknown cause affecting the eye and the facial skin. Ocular rosacea is often underdiagnosed if the ophthalmologist does not inspect the patient’s face adequately during the ocular examination. Severe ocular complications and blindness can occur if the treatment is delayed because of non-diagnosis of the rosacea. Here, we present a case of ocular rosacea in a 78-year-old Caucasian woman. Based on the ocular lesions, which preceded cutaneous involvement, she was misdiagnosed as having ocular cicatricial pemphigoid initially. This case emphasizes the difficulty in diagnosis when ocular findings precede those of skin manifestations, and rosacea should be kept in mind in the differential diagnosis of chronic cicatrizing conjunctivitis.